E-comic: saving money made fun / Aqilah Husna Shah Rullnizam ... [et al.] - Shah Rullnizam, Aqilah Husna; Asrul Efandi, Muhammad Harrith Daniel; Aidil, Muhammad Mirza Haziq; Mohd Musa, Nur Syamimi; Mohd Nordin, Noorain (Universiti Teknologi MARA, Kedah, 2023)
Introducing financial literacy early is crucial, and the digital age provides unique opportunities. The purpose of this e-comic is to act as a guideline that educates and empowers students about saving money in an interactive and visually appealing manner. The e-comic highlights the significance of teaching financial literacy at an early age and emphasizes the lifelong benefits of developing saving habits. It recognizes the need for innovative approaches to captivate the attention of students in the digital era. The e-comic is presented as an effective tool to engage and educate students. Through visually appealing illustrations and relatable characters, the e-comic creates an immersive experience that resonates with young learners. The storyline focuses on relatable scenarios and challenges that children encounter in their daily lives, providing practical examples of how saving money can make a positive impact. The e-comic encourages parental involvement through supplementary materials, sparking interactive conversations about saving money and fostering ongoing financial discussions at home. The accessibility and versatility of e-comics, allowing students to engage at their own pace on different devices. It provides narrative experiences for both beginner readers and language learners, fostering comprehension and sequencing skills without relying heavily on word decoding abilities. Through visually appealing illustrations and interactive features, the e-comic empowers young learners to develop financial literacy skills. With parental support, it cultivates lifelong saving habits, equipping students for financial success.